2021
DOI: 10.3390/app11199053
|View full text |Cite
|
Sign up to set email alerts
|

Canal Transportation and Volumetric Dentin Removal Abilities of Ni-Ti Rotary File Systems in Curved Primary Root Canals: CBCT Study

Abstract: Current improvements in nickel–titanium (Ni–Ti) rotary file systems have created a paradigm shift in the root canal therapy of primary teeth. Therefore, it is necessary to perform a comprehensive evaluation regarding the efficiencies of newly manufactured instruments for different parameters. The current study was conducted to evaluate the abilities of RaceEvo, R-Motion, ProTaper Gold (PTG) systems in curved primary root canals with regard to the patterns of canal transportation and volumetric dentin removal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
(39 reference statements)
0
3
0
1
Order By: Relevance
“…This insinuates that the maximum volume of dentine was removed by H files when compared with the other two NiTi rotary file systems. Islam et al 20 . and Barasuol et al 21 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This insinuates that the maximum volume of dentine was removed by H files when compared with the other two NiTi rotary file systems. Islam et al 20 . and Barasuol et al 21 .…”
Section: Discussionmentioning
confidence: 97%
“…This insinuates that the maximum volume of dentine was removed by H files when compared with the other two NiTi rotary file systems. Islam et al 20 and Barasuol et al 21 also checked the incidences of canal transportation with NiTi rotary files in comparison with hand files along with volumetric dentine removal. Both these studies found NiTi files to be a suitable and more efficient alternative to hand filing, which falls in line with the conclusions of similar studies carried out by other authors [22][23][24] ; it is, however, worth mentioning that these studies did not include any exclusive paediatric rotary files in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no published research on the three-dimensional (3D, e.g., volumetric) and two-dimensional (2D, e.g., canal transportation) e ciency of this newly developed rotary system on primary curved root canals. Thus, it is vital to evaluate relevant parameters, shaping quality, canal transportation, canal straightening, and unneeded hard dental tissue reduction during the curved root canals preparation in order to conduct successful long-term clinical trials using minimally invasive dentistry (14).…”
Section: Introductionmentioning
confidence: 99%
“…17 O tempo efetivo de instrumentação para os grupos mecanizados foi menor quando comparado aos grupos manuais, corroborando com os estudos de Mehlawat, et al 18 instrumento possui um efeito proporcional ao desvio radicular. 30,31 Nos demais grupos estudados, com instrumentos de conicidades menores, recomendadas para os dentes decíduos, devido ao seu alargamento no terço apical e maiores taxas de transporte de canais radiculares curvos, os resultados foram satisfatórios. 32,33 A quantidade de resina remanescente demonstra o desgaste das paredes dos canais após a instrumentação, indicando o nível de força empregado, que é proporcional ao nível de resina restante.…”
Section: Grupounclassified